ANALISIS TATA LETAK (LAYOUT) PROSES PRODUKSI AIR MINUM DALAM KEMASAN (AMDK) PADA PT. DIFUSI GOLDEN UTAMA DI BALIKPAPAN - Dewi Septiani; Anis Rachma Utary; Doddy Adhimursandi (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2018)
The purpose of this research is to find the production system and layout of bottled water production process (AMDK) at PT. Difusi Golden Utama in Balikpapan after conducting the implementation of line balancing concept. This research focuses on production system of bottled water in gallon packaging. Line balancing is a concept that makes an effort to make a balance in the production line of manufacturing function in order to create the continuity of production smoothly by classifying various production tasks into work stations by concerning with time balancing. To take the result of this research after implementing this concept, we need to know the minimum amount of required work center, the amount of idle time that occurs in each work station, the level of efficiency, and the level of idle time. Key words: Layout, Line Balancing, Efficiency, Idle Time